Automated analysis of lipid drug-response markers by combined fast and high-resolution whole cell MALDI mass spectrometry biotyping - Weigt, David; Abu Sammour, Denis; Ulrich, Timon; Munteanu, Bogdan; Hopf, Carsten (Scientific reports, 2018)
Recent advances in matrix-assisted laser desorption/ionization (MALDI) mass spectrometry have enabled whole cell-MALDI mass spectrometry biotyping of drug-treated cultured cells for rapid monitoring of known abundant pharmacodynamic protein markers such as polyacetylated histones. In contrast, generic and automated analytical workflows for discovery of such pharmacodynamic markers, in particular lipid markers, and their use in cellular tests of drug-like compounds are still lacking. Here, we introduce such a workflow and demonstrate its utility for cellular drug-response monitoring of BCR-ABL tyrosine kinase inhibitors in K562 leukemia cells: First, low-molecular mass features indicating drug responses are computationally extracted from groups of MALDI-TOF mass spectra. Then, the lipids/metabolites corresponding to these features are identified by MALDI-Fourier transformation mass spectrometry. To demonstrate utility of the method, we identify the potassium adduct of phosphatidylcholine PC(36:1) as well as heme B, a marker for erythroid differentiation, as markers for a label-free MALDI MS-based test of cellular responses to BCR-ABL inhibitors. Taken together, these results suggest that MALDI-TOF mass spectrometry of lipids and other low molecular mass metabolites could support cell-based drug profiling.
Gesehen am 03.07.2019